Skin wounds in a rural setting of Côte d’Ivoire: population-based assessment of the burden and clinical epidemiology - Toppino, Simone; N’Krumah, Raymond T. A. S.; Kone, Bognan Valentin; Koffi, Didier Yao; Coulibaly, Ismaël Dognimin; Tobian, Frank; Pluschke, Gerd; Stojković, Marija; Bonfoh, Bassirou; Junghanss, Thomas (PLoS neglected tropical diseases, 2022)
Data on the burden and clinical epidemiology of skin wounds in rural sub-Saharan Africa is scant. The scale of the problem including preventable progression to chronic wounds, disability and systemic complications is largely unaddressed.